Work life balance and work environment as determinants of employee performance: Empirical insights from a human resource perspective - Putri, Dewanti Natalia; Sumarsono, Tanto Gatot (Journal of Economic, Business & Accounting Research, 2025)
Background: This study aims to analyze the influence of Work Life Balance (WLB) and Work Environment (WE) on Employee Performance at Perumda Tirta Kanjuruhan. Methods: The method used in this research is quantitative, with data collection through a questionnaire distributed to 115 employees. The obtained data were analyzed using multiple linear regression analysis with SPSS software to measure the influence of each variable on employee performance. Findings: The results show that WLB has a positive and significant effect on Employee Performance, indicating that the better the balance between work and personal life, the higher the employee performance. Additionally, the Work Environment (WE) also proves to have a positive and significant impact on Employee Performance (EP), suggesting that a good atmosphere and working conditions can enhance employee productivity. Conclusion: Overall, this study concludes that both variables play an important role in improving employee performance at Perumda Tirta Kanjuruhan. Therefore, it is recommended that company management pay more attention to WLB aspects and create a conducive work environment to support optimal employee performance. Novelty/Originality of this article: The novelty of this article lies in its focus on the combined impact of WLB and WE on EP within a specific organizational setting, offering practical insights for organizational improvement and human resource management.